Trends and factors associated with immediate postnatal care utilisation in Ethiopia: analysis of the demographic and health surveys, 2011-2019 - Abdulaziz M Hussen; Aline Semaan; Binyam Tilahun; Özge Tunçalp; Diederick E Grobbee; Joyce L Browne (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background Globally, most maternal deaths occur during the first twenty-four hours after childbirth. Although different interventions have been implemented to improve maternal health care utilisation in Ethiopia, including immediate postnatal care, information regarding the change in immediate postnatal care utilisation over time is lacking. This study aimed to examine the trends of immediate postnatal care utilisation from the year 2011 to 2019 and to identify factors associated with immediate postnatal care utilisation using nationwide demographic and health survey data. # Methods The study was conducted using secondary data from Ethiopia Demographic and Health Survey (EDHS) in 2011 (n=4268), 2016 (n=4081), and 2019 (n=2159). The trend analysis was conducted using data from the three surveys, however, only the latest survey data were used for the analysis of factors associated with immediate postnatal care utilisation. Bivariable and multivariable logistic regression analysis was carried out to identify factors associated with immediate postnatal care utilisation. Odds ratio (OR) with a 95% confidence level (CI) was computed and adjustment was made to the survey design (i.e., weight, stratification, and clustering). # Results The percentage of women who received immediate postnatal check increased from 6.4% (95% CI=5.1-8.0) in 2011 to 16.3% (95% CI=14.3-19.0) in 2016 to 33.4 % (95% CI=28.6-39.0) in 2019. Moreover, health facility births and the percentage of women who had four or more antenatal care visits increased in this period. Having less than four (adjusted OR (aOR)=3.33; 95% CI=1.77-6.24) and greater than and equal to four antenatal care visits (aOR=7.19; 95% CI=3.80-13.56), and caesarean delivery (aOR=4.39; 95% CI=2.28-8.46) were factors positively associated with immediate postnatal care utilisation. On the other hand, giving birth at a health facility (aOR=0.04; 95% CI=0.02-0.07) was negatively associated with immediate postnatal care utilisation. # Conclusions The study showed consistent improvements in immediate postnatal care utilisation between 2011 and 2019. Despite the progress, the coverage remains low in Ethiopia, only reaching one-third of those who need it. More tailored and context-specific efforts across the continuum of maternal health care services are needed to improve the utilisation and quality of postnatal care.